2022
DOI: 10.3390/microorganisms10010108
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis and Immune System in Atherosclerotic Cardiovascular Disease (ACVD)

Abstract: Atherosclerosis is a leading cause of cardiovascular disease and mortality worldwide. Alterations in the gut microbiota composition, known as gut dysbiosis, have been shown to contribute to atherosclerotic cardiovascular disease (ACVD) development through several pathways. Disruptions in gut homeostasis are associated with activation of immune processes and systemic inflammation. The gut microbiota produces several metabolic products, such as trimethylamine (TMA), which is used to produce the proatherogenic me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 98 publications
1
18
0
Order By: Relevance
“…There are 100 trillion microbes in the human gastrointestinal tract, including 1000 different bacterial species comprising five phyla: Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Verrucomicrobia , collectively regarded as “gut microbiota” ( Li et al, 2014 ; Yoo et al, 2022 ). Gut microbiota and host symbiotic interactions commonly form an intestinal microenvironment to digest indigestible substances and secrete biologically active metabolites, and together maintain host energy metabolism, promote immune homeostasis, and sustain the normal function of distal organs ( Gregory et al, 2015 ; Lian W S et al, 2022 ).…”
Section: Gut Microbiota Disorders Target Mitochondria and Are Closely...mentioning
confidence: 99%
“…There are 100 trillion microbes in the human gastrointestinal tract, including 1000 different bacterial species comprising five phyla: Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Verrucomicrobia , collectively regarded as “gut microbiota” ( Li et al, 2014 ; Yoo et al, 2022 ). Gut microbiota and host symbiotic interactions commonly form an intestinal microenvironment to digest indigestible substances and secrete biologically active metabolites, and together maintain host energy metabolism, promote immune homeostasis, and sustain the normal function of distal organs ( Gregory et al, 2015 ; Lian W S et al, 2022 ).…”
Section: Gut Microbiota Disorders Target Mitochondria and Are Closely...mentioning
confidence: 99%
“…Atherosclerosis and the build-up of fatty streak and plaques are accelerated by aberrant levels of IL-6 and IL-10 [ 45 , 46 ]. The present study observed that the atherosclerosis plaque area of CO was higher than CF, with no difference being observed between LO and LF ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the interaction between the gut microbiota and host is crucial for the host to maintain normal intestinal and physical function [ 42 ], involving the maintenance of intestinal barrier integrity, the growth and regulation of the immune system, and normal homeostasis [ 43 , 44 ]. Commensal bacteria play an important role in regulating multiple physiological functions, including modulating the host’s gut mucosal barrier function, maintaining intact tight mucosal junctions, and regulating normal mucosal immunity [ 45 ].…”
Section: The Role Of the Gut Microbiota In Health And Diseasesmentioning
confidence: 99%